Radiation dose map at the Peruvian Antarctic Station - Osores, José (2016)
During January 2015, gamma-absorbed dose rates of natural radionuclides above ground were calculated throughout different areas of the Peruvian Antarctic Station “Machu Picchu”. The median outdoor gamma dose rate in air was determined as 43 ± 5 nGy/h. Using the data obtained in this study the median annual dose was found to be about 376 ± 44 μGy. These dose values are far below the doses reported in Peruvian territory due to the geographical location of the station.